Late Miocene freshwater mussels from the intermontane Chota Basin, northern Ecuadorean Andes. (January 2019) - Cadena, Edwin-Alberto; Casado-Ferrer, Ismael
Abstract: Prior to the development of the modern Amazonian drainage network during the Late Miocene-Early Pliocene, large areas of western Amazonia may have been occupied by an extensive lacustrine and wetland environment known as the Pebas and Acre systems. These depositional systems are thought to have formed in response to foreland subsidence east of the uplifting Andes. Based on the occurrence at a present-day elevation of 1600 m of fossil pearly freshwater mussels of the genus Anodontites (indet. species) in intermontane Chota Basin of northern Ecuador (the westernmost South American fossil record for this genus), we discuss their potential implications for understanding of westernmost limit of the Miocene wetland ecosystem and consequently a later timing for the regional uplift of the Eastern Cordillera. Graphical abstract: Image 1 Highlights: First record of Miocene freshwater mussels from the Chota Basin, Ecuador. South American westernmost Miocene record of Anodontites . Reinterpretation of the Chota Formation sedimentology.